2010
DOI: 10.1002/ep.10373
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and assessment of shipping emissions in the region of Ambarlı Port, Turkey

Abstract: Ships are significant air pollution sources as their high powered main engines often use heavy fuels. The major atmospheric components emitted are nitrogen oxides, particulate matter, sulfur oxides, carbon oxide, and toxic air pollutants. Shipping emissions cause serious effects on health and environment. These effects of emissions are seen especially in territorial waters, inland seas, canals, straits, bays, and port regions.In this article, exhaust gas emissions from ships in Ambarlı Port, which is one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…The first study was carried out in the Candarli Gulf and the second study at the Ambarli Port [25,26]. The objective of the studies was to estimate the amount of major atmospheric components emitted from heavy ship engines.…”
Section: Measurements Of Pm Concentration In Coastal Regionsmentioning
confidence: 99%
“…The first study was carried out in the Candarli Gulf and the second study at the Ambarli Port [25,26]. The objective of the studies was to estimate the amount of major atmospheric components emitted from heavy ship engines.…”
Section: Measurements Of Pm Concentration In Coastal Regionsmentioning
confidence: 99%
“…Tzannatos, estimated the shipping emissions and externalities for Port of Piraeus [19]. The shipping emissions were estimated by Saxe and Larsen (2004) for three Danish ports, Kılıç and Deniz (2010) for Izmit Gulf-Turkey, Deniz and Kilic (2010) for Ambarli Port, Deniz and Kilic (2010) for Candarli Gulf [2022]. …”
Section: Introductionmentioning
confidence: 99%
“…[10] calculated ship-related emissions in the Bosphorus and the Dardanelles and found that total emissions in these two regions are 700,386 t. [11] have calculated that the amount of ship-related emissions is 5,680,275 t in the Marmara Sea as of 2003. According to the study conducted by [12], the amount of ship-related emissions in Ambarlı Port of Istanbul is 82,344 tons. [13] calculated the total ship-related emissions in the Gibraltar Strait for the year 2007 and the amount is 1,447,171.77 t. [14] have studied on four Portuguese ports and found that ship-related emissions increased by an average of 20% between 1990 and 2014.…”
Section: Literature Reviewmentioning
confidence: 99%